Kemampuan Reseptif Anak Terlambat Bicara Pasca Terapi: Tinjauan Psikolinguistik - Desi Arni Natalina Br Siburian; Diah Ayu Lestari; Dicky Fahmi; Fatmawati Fatmawati (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
The problem of speech delay is the most common developmental disorder in children and is a serious issue that must be addressed right away. Despite the fact that children are able to truly comprehend what others are saying, speech delays can be identified by the child's correct word use, which is characterized by slurred pronunciation. This study focuses on receptive disorders of symbols, images, and sounds in order to determine the receptive ability of children who are late in speaking. This study utilized field research, case studies involving speech-impaired children, and data collection strategies. The descriptive research design and qualitative methodology of this study are used. 1) The following conclusions can be drawn from the analysis of the data: 1) Sensory, visual, and auditory perception disorders are present in children with slurred speech. 2) Sensory perception (recognition of symbols), visual perception (images), and auditory perception (sounds) are all affected in an unclear child. 3) The two most common types of phonological disorders are omission and replacement.